Faith as a basis of interaction of religion and politics - О. Г. Бортнікова (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2016)
The possibility of switching to two new approaches – meta-historical analysis of the changes theocratic and secular forms of domination and governance, as well as the creation of an institutional matrix of religious and political space of the state, which are in line with the traditions of Ukrainian religious studies theorizing. New methods of knowledge interaction between religion and politics in public life in one of the basic institutions – the phenomenon of faith. They are based on various grounds, its different systems concepts and different definitions and perspectives of the content review identified institutional changes in religion and politics. A comparison of these approaches is interesting also because they realized a fundamentally different way of constructing social knowledge about the interaction of religion and politics.